„Kochankowie z Ain Sakhri” w kontekście aktualnych badań nad kultem płodności na terenie Palestyny - Sobczak, Kamil (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
The main purpose of this article is to demonstrate the possible continuity between early Palestinian cults reconstructed from anthropomorphic figurines and later beliefs. Figurines from the major archeological cultures including: Kebarian, Natufian or Yarmukian indicate a common ceremony of religious character, possibly connected with the cult of fertility. In this contexts particularly noteworthy is so-called „Ain Sakhiri Lovers” figurine which is unique and interpreted as showing a sexual intercourse. By presenting some of the types of early Palestinian anthropomorphic figurines, the author would like to discuss possible connections between earliest artifacts of probable religious meaning with documented religious systems.